Dual-radical-based molecular anisotropy and synergy effect of semi-conductivity and valence tautomerization in a photoswitchable coordination polymer - Dai, Jing-Wei; Li, Yu-Qin; Li, Zhao-Yang; Zhang, Hai-Tao; Herrmann, Carmen; Kumagai, Shohei; Damjanović, Marko; Enders, Markus; Nojiri, Hiroyuki; Morimoto, Masakazu; Hoshino, Norihisa; Akutagawa, Tomoyuki; et al. (National Science Review, 2023)
Organic radicals are widely used as linkers or ligands to synthesize molecular magnetic materials. However, studies regarding the molecular anisotropies of radical-based magnetic materials and their multifunctionalities are rare. Herein, a photoisomerizable diarylethene ligand was used to form {[CoIII(3,5-DTSQ·-)(3,5-DTCat2-)]2(6F-DAE-py2)}·3CH3CN·H2O (o-1·3CH3CN·H2O, 6F-DAE-py2 = 1,2-bis(2-methyl-5-(4-pyridyl)-3-thienyl)perfluorocyclopentene), a valence-tautomeric (VT) coordination polymer. We directly observed dual radicals for a single crystal using high-field/-frequency (∼13.3 T and ∼360 GHz) electron paramagnetic resonance (EPR) spectroscopy along the c-axis, which was further confirmed by angle-dependent Q-band EPR spectroscopy. Moreover, a conductive anomaly close to the VT transition temperature was observed only when probes were attached at the ab plane of the single crystal, indicative of synergy between valence tautomerism and conductivity. Structural anisotropy studies and density functional theory (DFT) calculations revealed that this synergy is due to electron transfer associated with valence tautomerism. This study presents the first example of dual-radical-based molecular anisotropy and charge-transfer-induced conductive anisotropy in a photoswitchable coordination polymer.